International finance and open-economy macroeconomics - Gandolfo, Giancarlo (Springer, 2002)
"The international banking and currency crisis, and the advent of the Europe an Union, have made the subject of international finance one of the most important areas of economics for research and policy. Unfortunately, the older theories have been disappointing in their explanatory power, Both graduate students, researchers and staff economists in the European Central Bank, the independent central banks, the IMF and the World Bank will greatly benefit from an evaluation of the state of the art., Professor Gandolfo has written what will be a classic in international finance. His erudition, expository and technical skills are combined to fulfil these needs. He explain with great lucidity the strengths and weaknesses of various approaches, The exposition is carried out at several levels, similar to the way that Irving Fisher wrote his celebrated books. The literary part is clear, and the underlying intuition of the arguments is stressed. This is followed by a mathematical analysis, which uses the state of the art techniques, In this manner the reader can go from the intuition-literary argument to the formal derivations and proofs." -- BOOK JACKET.